EVALUATION OF SOME UNIFORMITY COEFFICIENTS FOR PRESSURIZED IRRIGATION SYSTEMS UNDER FIELD CONDITIONS IN DUHOK GOVERNORATE (IRAQI KURDISTAN) - SULAIMAN , ABDULSATTAR HAJI; KHALAF, AKRAM ABBAS (Journal of Duhok University, 2022)
The study was conducted in May–October 2021 within the Duhok University, Iraq, the study was carried out on the land adjacent to the College of Agricultural Engineering Sciences, in the fields of the “Seajay” village latitude 360 55’ 28’’N, longitude 420 52’ 36’’E and 640 (m.a.s.l), the objective of the study was focus on evaluating different uniformity coefficients proposed on investigating the effects of run time and field conditions on the results obtained utilizing those coefficients, a layout of 144 m2 was designed according to the length of lateral lines, 36 catch cans were positioned in a grid of 2 m apart. determining water distribution efficiency affected by different weather conditions during two- daily runs (morning &evening), and two time periods (May & June-July 2021) under operating pressures of (1.0 - 2.0) bar and riser heights of (1.0 - 2 m), solid site sprinkler with a single nozzle type (5mm) was used. The water caught in Cans was subjected to a three-way (ANOVA) table using (LSD) test, the study concluded that riser heights of 1 m had the optimum (CU & DU%) at 2 bar (operating pressure) to reduce water losses, and the results showed that highly significant differences between the means of (CU & DU%) coefficients in (May 2021) at various run times (morning & evening), in time it was shown highly significant differences between the means of all parameters with (PELQ %) coefficients in the (June –July 2021) period. It is not suggested to run the sprinkler irrigation system at wind speeds of (2.6 - 3.6 ms-1)